The anti-cataract molecular mechanism study in selenium cataract rats for baicalin ophthalmic nanoparticles - Li N; Han Z; Li L; Zhang B; Liu Z; Li J (Dove Medical Press, 2018)
Nan Li,1–3,* Zhenzhen Han,1,2,4,* Lin Li,1,2 Bing Zhang,1–3 Zhidong Liu,1–3 Jiawei Li1,2 1Tianjin State Key Laboratory of Modern Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 2Institute of Traditional Chinese Medicine,Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 3Engineering Research Center of Modern Chinese Medicine Discovery and Preparation Technique, Ministry of Education, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 4Baokang Hospital, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China *These authors contributed equally to this work Purpose: The objective of this study was to investigate the effects of the solid lipid nanoparticles of baicalin (BA-SLNs) on an experimental cataract model and explore the molecular mechanism combined with bioinformatics analysis.Materials and methods: The transparency of lens was observed daily by slit-lamp and photography. Lenticular opacity was graded. Two-dimensional gel electrophoresis (2-DE) was employed to analyze the differential protein expression modes in each group. Proteins of interest were subjected to protein identification by nano-liquid chromatography tandem mass spectrometry (LC–MS/MS). Bioinformatics analysis was performed using the Ingenuity Pathway Analysis (IPA) online software to comprehend the biological implications of the proteins identified by proteomics.Results: At the end of the sodium selenite-induced cataract progression, almost all lenses from the model group developed partial nuclear opacity; however, all lenses were clear and normal in the blank group. There was no significant difference between the BA-SLNs group and the blank group. Many protein spots were differently expressed in 2-DE patterns of total proteins of lenses from each group, and 65 highly different protein spots were selected to be identified between the BA-SLNs group and the model group. A total of 23 proteins were identified, and 12 of which were crystalline proteins.Conclusion: We considered crystalline proteins to play important roles in preserving the normal expression levels of proteins and the transparency of lenses. The general trend in the BA-SLN-treated lenses’ data showed that BA-SLNs regulated the protein expression mode of cataract lenses to normal lenses. Our findings suggest that BA-SLNs may be a potential therapeutic agent in treating cataract by regulating protein expression and may also be a strong candidate for future clinical research. Keywords: BA-SLNs, 2-DE patterns, nano-LC–MS/MS, IPA, SDS-PAGE